Isolation and Identification of Bacteria Causing Urinary Tract Infections in Pregnant Women in Tarhuna city - Awatif Ahmed Mohammed Eshtiwey; Aedah Ahmed Mohamed Eshtiwey; Tasneem salem Alzawwam; Asmhan Meftah Sultan; Sorour Khalil Omar (Journal of Libyan Academy Bani Walid, 2025)
Abstract: This study investigated the bacterial pathogens responsible for urinary tract infections (UTIs) among pregnant women in Tarhuna, Libya· A total of 72 urine samples were collected and analyzed using culture methods, biochemical tests, and MALDI-TOF confirmation where available· The findings revealed that Staphylococcus aureus was the most frequently isolated bacterium (45·5%), followed by Escherichia coli (20%), Klebsiella spp· (14·5%), and other pathogens such as Enterococcus spp·, Proteus spp·, and Streptococcus· The results showed that Nitrofurantoin and Ciprofloxacin were the most effective antibiotics, while high resistance rates were observed against Amoxicillin-Clavulanic acid and Trimethoprim-Sulfamethoxazole· These outcomes highlight the need for routine urine culture screening, targeted antibiotic stewardship, and continuous surveillance of antimicrobial resistance patterns· The study concludes that urinary tract infections remain a significant health problem during pregnancy, requiring proper diagnosis, treatment, and preventive strategies to minimize maternal and fetal complications.